2014
DOI: 10.6007/ijarems/v3-i6/1351
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Conflicts: Causes, Effects and Remedies

Abstract: This paper examines the causes, effects and remedies of organizational conflict. What are the things that lead to conflicts in organizations? The study found out that like other terms, conflict generates considerable ambivalence and leaves many scholars and administrators quite uncertain about (1) its meaning and relevance; and (2) how best to cope with it. Conflicts are inevitable in human life. It is also inevitable in organizations or even between nations. Conflict is an inseparable aspect of people's as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 15 publications
(8 reference statements)
1
51
0
7
Order By: Relevance
“…This may lead to nurses disowning the agreement. Coming up with a conducive and favourable solution requires engagement through dialogue and negotiation to enhance trust among parties (Omisore & Rashidat Abiodun 2014:134). Kinnander (2011:42) reported that a fair process requires mutual agreement, wherein everyone is allowed to have his or her say in the process of conflict resolution and is involved in decision-making.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…This may lead to nurses disowning the agreement. Coming up with a conducive and favourable solution requires engagement through dialogue and negotiation to enhance trust among parties (Omisore & Rashidat Abiodun 2014:134). Kinnander (2011:42) reported that a fair process requires mutual agreement, wherein everyone is allowed to have his or her say in the process of conflict resolution and is involved in decision-making.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Moreover, a better understanding of the causes of organizational conflict will help in adopting suitable strategies or mechanisms to resolve it. Some researchers such as [10][11][12][13][14] have mostly classified the causes of organizational conflict under three categories which include; task conflict, interpersonal conflict and procedural conflict. Task conflict occurs when an employee is unclear about what is expected of him/her to perform, or how to perform the assigned task, task interdependent and/or when the task given to employees working in a group is not clearly defined by the supervisor.…”
Section: What Is Organizational Conflict?mentioning
confidence: 99%
“…From 2000 to 2003 was the initial stage of gold mining activities in Poboya. At this stage it was found that there were only around 50 local people who carried out mining activities in the region using sieve technology [9]. Furthermore, massive mining activities occurred in 2013 which caused a change in the shape of the area.…”
Section: Transfer Of Employmentmentioning
confidence: 99%
“…This can cause a very large chance of conflict because conflict will arise when the distribution of an opportunity is uneven and controlled by a certain group [7]. Likewise, the conflict that occurred in Poboya in 2010 can be a manifestation of the social and cultural impacts that arise as a result of mining activities causing a high flow of people from outside the area to mine, resulting in friction due to inappropriate distribution of land ownership [9]. For more details related to these problems, see the following table: Table 2, the existence of the gold mining activity in Poboya has given social and cultural impacts for the local community.…”
Section: Fig 2 the Processing Of The Poboya Gold Minementioning
confidence: 99%